URIC ACID CONTENT, RENIN CONCENTRATION IN PATIENTS WITH PRE-ECLAMPSIA, DEPENDING ON THE LEVEL OF VITAMIN D AND CHARACTERISTICS OF EPIDURAL ANALGESIA IN LABOR - E. V. Oreshnikov; E. N. Vasilieva; L. I. Maltseva; T. G. Denisova (Вестник анестезиологии и реаниматологии)
The objective: to investigate the correlation of renin concentration and uric acid content in pregnant women with pre-eclampsia and vitamin D deficiency and their impact on the course of pregnancy, childbirth, and infant status.Subjects and methods. The content of uric acid, vitamin D, endothelin and renin concentration were studied in pregnant women with pre-eclampsia and the control group; enzyme immunoassay and spectrophotometric tests were used. Venous blood was used as a specimen for tests.Results. Hyperuricemia (435.61 ± 24.05 μmol/l) and a 10-fold increase of renin concentration were observed in patients with severe pre-eclampsia and vitamin D deficiency (11.23 ± 1.60 ng/ml). Vitamin D deficiency is associated with a higher need for epidural administration of local anesthetics during labor analgesia in patients with pre-eclampsia versus the control group; it is also associated with unfavorable perinatal outcomes.Conclusions. The following was detected in the patients with pre-eclampsia: low levels of vitamin D, hyperuricemia, elevated blood renin concentration, which was associated with the severity of pain and increased blood pressure. For adequate analgesia and blood pressure control during labor, they needed a higher rate of local anesthetic administration. Perhaps, replenishing vitamin deficiencies during pregnancy may improve perinatal outcomes.